List of hotels in Chicago (1968)
This document provides a listing of hotels in Chicago housing state and territorial delegations, including hotel names, addresses, phone numbers, and assigned states. It includes a detailed breakdown of which delegation is assigned to each hotel, covering all states as well as the District of Columbia and U.S. territories. The final page presents a chart of delegate vote totals by state and territory, along with a total convention vote count.